Geothermal solid waste derived Ni/Zeolite catalyst for waste cooking oil processing. (January 2022) - Satriadi, Hantoro; Pratiwi, Isdayana Yogi; Khuriyah, Malikhatul; Widayat,; Hadiyanto,; Prameswari, Jedy
Abstract: The main aim of this work was to develop a sustainable Ni/Zeolite catalyst derived from geothermal solid waste for waste cooking oil processing. The effects of catalyst concentration and operation temperature on the transesterification process for biodiesel production which used waste cooking oil as feedstock were investigated to determine the optimum biodiesel process condition. Results have shown the synthesized Ni/Zeolite catalyst was granular in shape and crystalline with increased surface area and pore volume, 80.661 m 2  g −1, and 0.123 cc g −1 respectively. Meanwhile, the highest biodiesel yield obtained was 89.4 % at 3 % w/w Ni/Zeolite catalyst addition and 60 °C operating temperature. The reusability of the synthesized catalyst was also investigated, with results showing the biodiesel yield decreasing to 73.3 % after three cycles. Highlights: Catalyst showed promising performance in biodiesel production. Impregnation of Ni to the zeolite catalyst improved the surface area and pore volume. 3 % w/w catalyst weight and 60 °C operating temperature give highest biodiesel conversion, 89.4 %.